Equality in the Qur'an: Analysis of the Interpretation of QS. Ali ʻImran [3]:195 and Its Relevance to Contemporary Gender Discourse - Fina Nuriah Rohimatil Umah; Ahmad Isnaeni; Yusuf Baihaqi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study departs from the numerous discussions on gender equality that are always echoed by feminists. The discourse on gender equality in contemporary Islamic discourse continues to undergo dynamics, especially when some circles consider that the interpretation of the Qur'an still contains gender bias. Based on considerations of controversy and life context, this study focuses on examining the interpretation of QS. Ali ʻImran 3: 195 and its relevance to the discourse on gender equality. This study is a pure literature study with primary data from QS. Ali ʻImran 3: 195. This study also uses documentation data collection techniques and descriptive and content analysis data analysis. The results of this study show that this verse emphasizes that Allah and His Messenger do not discriminate between human deeds based on gender. Both men and women have the same position and status in the eyes of Allah as long as they are believers and are willing to fight in the way of Allah. Allah will give the same reward for their deeds without favoring one gender over another. This is certainly relevant to the gender equality that is being promoted today, that there is no difference between the deeds/actions of men and women. All of them must be valued and given the same appreciation.